PERCEPTION AND MOTIVATION OF CHRISTIAN STUDENTS TO CHOOSE MUHAMMADIYAH UNIVERSITY: PLURALISTIC EDUCATIONAL PERSPECTIVE OF MUHAMMADIYAH - Pribadi, Imam; Asriany, Asriany (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract: Religious plurality must be interpreted as plurality and multireligiousism in the nation's life and state. This research aimed to investigate Christian students' perception and motivation to study at Muhammadiyah University in Palopo. It was qualitative research with a phenomenological approach, which was conducted at Muhammadiyah University of Palopo. Five non-Muslim students were selected based on the purposive sampling technique, and the researchers became the main instruments. Other supporting instruments were interview guidelines, observation sheets, and tape recorders. The data collection techniques used are observation, in-depth interview, and documentation. The researchers made data reduction, data display, and drawing conclusions or verification in analyzing the data. The findings obtained revealed that Christian students' perception and motivation in enrolling Muhammadiyah University of Palopo was majorly affected by the support of parents, families, self-motivation, and their major at Muhammadiyah University of Palopo. Abstrak: Pluralitas agama merupakan suatu hal yang harus dimaknai sebagai kemajemukan dan multireligius dalam kehidupan berbangsa dan bernegara. Penelitian ini bertujuan untuk mengetahui persepsi dan motivasi mahasiswa Kristen dalam memilih Universitas Muhammadiyahdi Palopo. Pendekatan metode yang digunakan adalah kualitatif yang bercorak fenomenologi. Penelitian ini dilakukan di Universitas Muhammadiyah Palopo. Jumlah sampel yang digunakan yaitu 5 mahasiswa non muslim, dengan teknik pemilihan purposive sampling. Instrumen dalam penelitian ini yaitu peneliti itu sendiri sebagai instrumen utama, adapun instrument pendukung yaitu pedoman wawancara, lembar observasi, dan tape recorder. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara mendalam (indepth interview), dan dokumentasi. Adapun analisis data yang digunakan yaitu reduksi data, displaydata dan pengambilan kesimpulan atau verifikasi. Hasil penelitian yang diperoleh bahwa Persepsi dan motivasi mahasiswa Kristen dalam memilih Universitas Muhammadiyah Palopo sebagian besar dipengaruhi oleh dukungan orang tua, keluarga, motivasi dalam diri, dan jurusan yang diinginkan ada di Universitas Muhammadiyah Palopo.